(untitled) (Revista Brasileira Multidisciplinar, 2011)
Chagas disease, discovered more than one century ago by Carlos Chagas, is still a serious Public Health problem. It is considered an extremely neglected disease, for it affects specially the population of developing countries. The patients with this disease have, in the great majority, low income and, for not representing market, they are excluded from the aims and efforts of research and development of pharmaceutical industries. About 8 to 11 million people may be infected with Trypanosoma cruzi, the etiological agent of the disease and about 100 million people are in risk in Latin America. The treatment of the disease is still a challenge, for only two nytroheterociclic drugs are commercialized in the world: nifurtimox and benznidazole, being this last one, the only available drug in the Brazilian market. However, these drugs are active only in the acute phase of the disease, and the treatment is not efficient in patients in the chronic phase. Consequently it is relevant to develop efficient anti-chagas compounds, particularly for the chronic phase of the disease. This paper discusses the importance of latency for the development of new pro-drugs. The literature describes several methodological techniques that have enabled significant advances in the planning and development of new anti-chagas agents, with emphasis on the search for pro-drugs that allow the enhancement of drug matrices.